Sustainable Health and Wellbeing in the European Union - Gavurova, Beata; Megyesiova, Silvia (Frontiers in Public Health, 2022)
Background: Altogether 17 Sustainable Development Goals represents a group of goals which are an urgent call for action to end poverty, protect the planet and ensure prosperity for all. Goal 3 is crucial in terms of good health and well-being. The main aim of this study is to analyse and to evaluate differences among indicators of SDG 3: Sustainable health and well-being in the EU countries. Methods: The status and development of the EU Member States regarding their successes or failures in term of Goal 3 was subjected to analysis. Altogether eleven indicators were used to rank the EU countries using the TOPSIS and ranking methods. The ranks were assigned to the countries in two periods. The first period is related to the time span from 2010 till 2014 and the second period from 2015 till 2019. Results: The EU countries achieved a positive development in ten of eleven indicators that monitor the achievement of the EU in terms of Goal 3. The only variable that changed in a negative way was the obesity rate. Positively must be rated the decline of the standardized preventable and treatable mortality that declined from 317.3 in the first period to 295 in the second period, the drop of the population weighted annual mean concentration of fine particulate PM2.5 from 16.4 to 13.6 μg/m3, but also the increase of the share of people with good or very good perceived health that was combines with a decrease of the self-reported unmet need for medical examination and care. The best rated country in terms of Sustainable Development Goal 3 was in both periods Sweden while the worst rated country was Latvia. Conclusions: Governments and institutions in the EU can do a lot to increase the accessibility and quality of the health care system but everybody should try to do the best to reduce some of the risk factors like smoking or obesity, to try live healthier and to lead a healthy lifestyle and so help to achieve higher ambitions in terms of Sustainable health and well-being.